Analisis Komunikasi Pemasaran terhadap Keputusan Pembelian Produk Sepeda Motor Honda Beat pada Pt. Indostar Sukses Mandiri - Tamado Simon Sagala (Yayasan Literasi Sains Indonesia, 2024)
Consumers' purchase decisions are often influenced by a company's marketing communications such as advertising and direct marketing. PT. Indostar Sukses Mandiri has active marketing communications activities including advertising and interactive direct marketing. Purpose of this study is to determine the influence of advertising and direct marketing on the purchase decision of Honda Beat motorcycles in PT. Indostar Sukses Mandiri which is Indostar Sukses Mandiri. Sukses Mandiri is located at Jalan Karya No. 184, Sei Agul, Medan Barat, Medan City. The target population of this study is 93 customers of PT Indostar Sukses Mandiri. The sample of this study is 48 people and the method of selection is purposive sampling. The methods of data collection in this study are questionnaire and document analysis. Multiple regression analysis using SPSS 23 program was used as data analysis method in this study. The results of this study show that partial promotion has a positive and significant effect on purchase decision. It was also found that direct marketing has partial positive and significant effect on purchase decision of Honda Beat motorcycles in PT. Indostar Sukses Mandiri.